PS-C15-11: HYPERTENSION AND ITS CORRELATES AMONG SCHOOL ADOLESCENTS IN DELHI. (January 2023) - Grover, Shekhar
Abstract : Background: Hypertension is fast emerging as a major health problem amongst all school adolescents, particularly in urban areas. Regular screening of the students for this is required for preventing the emergence of complications later in life. Therefore the present study was undertaken with the objective to determine the prevalence of hypertension amongst urban school adolescents and its correlation with anthropometric measurements. Methods: A cross sectional study was conducted in a school in Central Delhi involving all 315 students of 9th and 11th standard. A proforma was filled by the students and anthropometric measurements along with blood pressure BP measurements were taken for each student. Data were analyzed using Epi info 2005 and SPSS 16.0. Results: Out of the total 315 students, 208 or 66% were boys and 107 or 34% were girls and the mean age was 14.31 SD 0.96 years. The overall prevalence of malnutrition was 24% and boys were found to be more obese as compared to girls. There were 5 students 1.6% who were found to have systolic hypertension while 17 or 5.4% were found to have diastolic hypertension while 4.1% n = 13 of the participants were systolic pre hypertensive and 26% n = 82 were in the stage of diastolic pre hypertension. Body mass index and gender were found to be independent predictors of systolic hypertension. Conclusions: Prevalence of hypertension and pre hypertension was high amongst the school children. BP check ups for children and adolescents are thus recommended to take remedial action on time